Hubungan Pengetahuan dan Motivasi Mahasiswa Terhadap Upaya Pencegahan Kanker Serviks di Stikes Yahya Bima - Wahidah, Wahidah (Barongko: Jurnal Ilmu Kesehatan, 2023)
Background: According to Basic Health Research data for 2018, the prevalence of cancer in Indonesia shows an increase from 1.4 per 1000 population in 2013 to 1.79 per 1000 population in 2018. Purpose: To determine the relationship between student knowledge and motivation towards cervical cancer prevention at STIKES Yahya Bima. Method: The type of research used in this research is an analytical survey with a cross-sectional approach. Research subjects were students who met the inclusion criteria. Determination of the sample was done by purposive sampling. Data were obtained from questionnaires and analyzed univariately and bivariately. Univariate analysis in the form of frequency distribution is presented in table form using the Chi Square test. Results: The level of knowledge of students at STIKES Yahya Bima regarding efforts to prevent cervical cancer was obtained with a value of ρ = 0.001. Thus, Ho is rejected, Ha is accepted or there is a relationship between the level of student knowledge and efforts to prevent cervical cancer. Student motivation at STIKES Yahya Bima towards cervical cancer prevention efforts obtained a value of ρ = 0.003 Thus Ho is rejected Ha is accepted or there is a relationship between student motivation and cervical cancer prevention efforts.